Islamic Legal Philosophy Approach in Preventing the Culture of Bribery in Indonesia - Ningrum, Maya Puspita; Roza, Ahmad Fadly; Sari, Komala (Jurnal Penelitian Medan Agama, 2024)
Indonesia a state of law based on Pancasila and the 1945 Constitution, upholds human rights and equality before the law. Corruption damages development, with eradication that is not optimal. Professional and transparent law enforcement is needed. The approach of Islamic law philosophy in preventing corruption needs to be explored further. This research is important in enriching the discourse on corruption prevention, providing a foundation for policymakers, religious institutions, and the community. This research uses a normative law approach with literature study, exploring written law, including legal theory, history, and philosophy. Data was obtained from legal regulations, Islamic legal philosophy literature, and legal encyclopedias. Qualitative analysis was carried out using a deductive method, linking the principles of Islamic law to the reality of bribery culture in Indonesia. The perspective of legal sociology is also used to understand the interaction between law and society. The goal is to provide a comprehensive understanding of the prevention of bribery culture. Corruption, including bribery, is considered to violate the principles of Islamic law, such as justice and prevention of damage. Islamic legal philosophy emphasizes individual integrity and public participation in the prevention of corruption. This approach, together with legal sociology, can form a comprehensive strategy to address corruption in Indonesia. Changes in the substance of the law, law enforcement institutions, and an anti-corruption culture are needed to achieve these goals. The philosophical approach of Islamic law in the prevention of bribery emphasizes the improvement of individual morals and the principle of monotheism. The prohibition of bribery is based on justice and prevention of damage. Integration with legal sociology is necessary to formulate effective prevention strategies. Community stability can be improved through strengthening morals and integrity as well as public participation in overcoming the culture of bribery. With this approach, the hope of eradicating bribery in Indonesia becomes more realistic.